Volunteers or governors? Rethinking civil society in Turkey beyond the problematic of democratization: the case of TEGV - İpek, Yasemin. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
This study basically argues that the context of neo-liberal policies and the parallel weakening of the state are considerably significant processes in interpreting civil society in post-1980 Turkey. Based on this argument, it offers to go beyond the problematic of democratization which has been the focus of the academic discussionson civil society. Particularly after the Marmara Earthquake of 1999, the civil society organizations (CSOs) which provide social services to people and support the state began to be promoted. Thus, these voluntary organizations and volunteerism have become decisive in defining the meaning and content of civil society. Increasing cooperation between the state, private companies and citizens for effective government has transcended the supposed distinction between the state and civil society. It is also the same process through which the middle classes have begun to raise their voices in social and political life via these organizations and to reproduce the Kemalist discourse on modernity. This case study on TEGV (Türk Egitim Gönüllüleri Vakfı) analyzes both the complexities of the process whereby CSOs areincreasingly becoming a part of our lives on a wide range of areas, and the opening up of a "space of intervention" for the discourse of the middle class in Turkey. The official discourse of TEGV is interpreted alongside in-depth interviews conductedwith the volunteers working there. In this process of interpretation, I problematized the projects and techniques deployed in TEGV̕s programs through the analytical tools provided by governmentality studies. This problematization delineates the discursive formation of TEGV which harmonizes the Kemalist aspiration to modernize the country with the neo-liberal emphasis on self-responsibility and selfconfidence. Besides, the complexities of volunteer subjectivity are discussed at length, leading us to rethink civil society and state especially in post-1990 Turkey.
Keywords: Nonprofit organizations -- Management.; Voluntarism -- Management.; Volunteers.; Civil society -- Turkey.